The Influence of Patient Attendance for 5 Years in Prolanis (Chronic Disease Management Program) on Body Mass Index and Chronic Disease Parameters - Fadillah, Reza Arif; Afriandi, Irvan; Arya, Insi Farisa Desy (Review of Primary Care Practice and Education, 2024)
Background: Chronic diseases such as diabetes and hypertension are one of the biggest causes of death in the world and in Indonesia. Social Insurance Administration Organization or Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan, a health insurance in Indonesia, has a chronic disease management program or prolanis Patients who follow the prolanis program follow the prolanis program process for years. Objective: This study looks at whether patients who have followed the prolanis program for 5 years from 2019 to 2023 get good output results of health parameters such as blood pressure, HbA1c, Total Cholesterol, LDL, HDL, Ureum, Creatinine, and eGFR. Methods: This research method is a quantitative analytic retrospective on 151 patients who participated in the prolanis program during the period 2019 to 2023 with a pre-post retrospective research design. Normality tests were performed on all variables to determine the distribution of data distribution and bivariate analysis.  The parameters assessed were Body Mass Index, HbA1c, Total Cholesterol, LDL, HDL, Triglycerides, Ureum, Creatinine, eGFR and Blood Pressure. Results: The results showed that significant differences occurred in the values of HbA1c, ureum, creatinine, and eGFR parameters in the group of patients with attendance ≥40 months. The Δ value from 2023 to 2019 has a significant difference (p-value <0.05) based on the HbA1c variable which increased in value in the ≥40 months attendance group, and decreased in value in the <40 months attendance group, then there was no significant difference in the value of other parameters in all attendance groups. For hypertension, the highest incidence of hypertension occurred in attendance <40 months less than attendance ≥40 months so that there was no relationship between attendance and blood pressure values in the last year (year 2023). Conclusions: It was concluded that attendance for 5 years with attendance ≥ 40 months was beneficial in maintaining eGFR function compared to attendance < 40 months. However, it has not been proven to be beneficial in maintaining the stability of HbA1c in the attendance group ≥ 40 compared to the attendance group < 40 months. Although there was an increase in ureum and creatinine, attendance ≥ 40 months proved to be able to maintain the stability of ureum and creatinine in normal numbers. From the results of the study, the highest incidence of hypertension occurred in attendance ≥40 months compared to attendance <40 months, so there is no relationship between the number of attendance with blood pressure values.